Elementos restaurativos del cumplimiento penitenciario - Cervelló Donderis, Vicenta (Eguzkilore, 2022)
This paper analyzes the Restorative Justice as a service for the victim and a opportunity for the resocialitation of the ofender from the restorative possibilities during the execution of theimprisonment and its relationship with prison treatment. To get it, the characteristics of restorativeprograms after the sentence and the legal penitentiary instruments which facilitate the reparatory agreements with the victim and which humanize the imprisonment are exposed